Effects on School Enrollment and Performance of a Conditional Cash Transfer Program in Mexico - Dubois, Pierre; de Janvry, Alain; Sadoulet, Elisabeth (Journal of Labor Economics, 2012)
We study the effects of the Mexican conditional cash transfer program Progresa on school enrollment and performance in passing grades. We develop a theoretical framework of the dynamics of the educational process including endogeneity and uncertainty of school performance. Using a randomized experiment implemented under Progresa, we identify the effect of the program on enrollment and performance in the first year of the program. We find that the program had a positive impact on school enrollment at all grade levels, whereas for performance it had a positive impact at the primary school level but a negative impact at the secondary level.